2020
DOI: 10.3390/antiox9121170
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Scattered Versus Scanned Proton Beams on Normal Tissues in Total Body Irradiated Mice: Survival, Genotoxicity, Oxidative Stress and Inflammation

Abstract: Side effects of proton therapy are poorly studied. Moreover, the differences in the method of dose delivery on normal tissues are not taken into account when proton beams are scanned instead of being scattered. We proposed here to study the effects of both modalities of proton beam delivery on blood; skin; lung and heart in a murine model. In that purpose; C57BL/6 mice were total body irradiated by 190.6 MeV proton beams either by Double Scattering (DS) or by Pencil Beam Scanning (PBS) in the plateau phase bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Future investigations are strongly needed to explain the differences in biological responses observed between PBS and DS. Indeed, differences were also recently shown in terms of genotoxicity, oxidative stress and inflammation in various organs in total body irradiated C57BL/6 mice exposed to scattered versus scanned proton beams 52 . These findings pointed out the absolute need to adapt the PT protocols according to the type of scanning.…”
Section: Discussionmentioning
confidence: 87%
“…Future investigations are strongly needed to explain the differences in biological responses observed between PBS and DS. Indeed, differences were also recently shown in terms of genotoxicity, oxidative stress and inflammation in various organs in total body irradiated C57BL/6 mice exposed to scattered versus scanned proton beams 52 . These findings pointed out the absolute need to adapt the PT protocols according to the type of scanning.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, on the one hand, there is some recent experimental evidence that large doses and dose rate variations may play a significant role in determining the response of some organs and tissues to irradiation (see Section 2.1 about the FLASH effect). On the other hand, major differences have recently been observed between scattered or scanned beams (in particular for protons), such as in late skin gene expression or according to the organs considered in terms of genotoxicity, antioxidant capacity, or inflammatory cytokines [ 68 , 69 ], which could also be related to the dose rate even if we are not in the application range of the FLASH effect. The role of the immune system and the microenvironment in the response to radiation exposure is also mentioned as a possible explanation of the FLASH effect [ 44 ].…”
Section: Very High-energy Electrons and Their Potential Application In Radiation Therapymentioning
confidence: 99%
“…Troeller et al [24] unambiguously demonstrated that 3D-RT-based NTCP models imperfectly work for IMRT. The validity of applying NTCP models that have been based on photon techniques for IMPT irradiation is uncertain; DNA damage with proton therapy is not fully understood but is different from classical photon beam radiobiological effects and might differ between passive scattering and pencil beam scanning proton beams [25]. Mee et al [26] stressed that NTCP models should theoretically be adjusted with the acquisition of new clinical data and updating of existing databases (which poses the problem of observation delay); finally, ∆NTCP thresholds could be prospectively adjusted based on clinical feedback and on increasing proton therapy treatment capacity.…”
Section: Limitations Of Ntcp Modelsmentioning
confidence: 99%